2001
DOI: 10.1086/318364
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Ionization Structures in Planetary Nebulae: Confronting Models with Observations

Abstract: Around 50 planetary nebulae (PNe) are presently known to possess "small-scale" low-ionization structures (LISs) located inside or outside their main nebular bodies. We consider here the different kinds of LISs (jets, jet-like systems, symmetrical and non-symmetrical knots) and present a detailed comparison of the existing model predictions with the observational morphological and kinematical properties. We find that nebulae with LISs appear indistinctly spread among all morphological classes of PNe, indicating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
148
2
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(158 citation statements)
references
References 69 publications
5
148
2
3
Order By: Relevance
“…Narrow-band [NII] or [SII] images are useful in revealing LIS, but they are best isolated by constructing an Hα+[NII]/[OIII] image that removes density variations to highlight just changes in ionisation. Gonçalves et al (2001) reviewed PNe exhibiting LIS, their kinematics and their purported formation mechanisms (see also Gonçalves 2004).…”
Section: Low-ionisation Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Narrow-band [NII] or [SII] images are useful in revealing LIS, but they are best isolated by constructing an Hα+[NII]/[OIII] image that removes density variations to highlight just changes in ionisation. Gonçalves et al (2001) reviewed PNe exhibiting LIS, their kinematics and their purported formation mechanisms (see also Gonçalves 2004).…”
Section: Low-ionisation Structuresmentioning
confidence: 99%
“…Exter et al 2003) even though their velocities not substantially different from their nebulae (Gonçalves 2004). We describe knots as unresolved or small LIS with an aspect ratio of unity, and filaments as knots with an aspect ratio larger than unity (Gonçalves et al 2001). We adopt a stricter definition of jets to be opposing polar outflows located well outside the main nebula and with typically lower surface brightness than equatorial filaments (e.g.…”
Section: Low-ionisation Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Gonçalves et al 2001;Corradi 2006). Miszalski et al (2009b) suggested close binaries play a strong role in the formation of LIS after finding an elevated occurrence of LIS in post-CE nebulae.…”
Section: Low-ionisation Filamentsmentioning
confidence: 99%